2019
DOI: 10.1111/jzs.12285
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial phylogenetics of the goshawkAccipiter[gentilis] superspecies

Abstract: The Northern Goshawk Accipiter gentilis is a medium‐sized bird of prey inhabiting boreal and temperate forests. It has a Holarctic distribution with 10 recognized subspecies. Traditionally, it has been placed within the Accipiter [gentilis] superspecies, together with Henst's Goshawk A. henstii, the Black Sparrowhawk A. melanoleucus, and Meyer's Goshawk A. meyerianus. While those four taxa are geographically separated from each other, hence referred to as allospecies, their phylogenetic relationships are still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…A weakness of observational inheritance data is that parentage can only be confirmed with certainty with genetic data. However, extra‐pair paternity is a rare phenomenon in socially monogamous raptors with proportions ranging from 1.3% in the closely related northern goshawk ( Accipiter gentilis , Gavin et al ., 1998, Rutz, 2005, Kunz et al ., 2019) to 0% in merlin ( Falco columbarius , Warkentin et al ., 1994) to 3–11.2% in American kestrels ( Falco sparverius , Villarroel, Bird & Kuhnlein, 1998). In Cooper's hawks ( Accipiter cooperii ), extra‐pair paternity can be considered as high as 19.3% of all nestlings (Rosenfield et al ., 2015), but such high levels of extra‐pair paternity seem to be an exception.…”
Section: Discussionmentioning
confidence: 99%
“…A weakness of observational inheritance data is that parentage can only be confirmed with certainty with genetic data. However, extra‐pair paternity is a rare phenomenon in socially monogamous raptors with proportions ranging from 1.3% in the closely related northern goshawk ( Accipiter gentilis , Gavin et al ., 1998, Rutz, 2005, Kunz et al ., 2019) to 0% in merlin ( Falco columbarius , Warkentin et al ., 1994) to 3–11.2% in American kestrels ( Falco sparverius , Villarroel, Bird & Kuhnlein, 1998). In Cooper's hawks ( Accipiter cooperii ), extra‐pair paternity can be considered as high as 19.3% of all nestlings (Rosenfield et al ., 2015), but such high levels of extra‐pair paternity seem to be an exception.…”
Section: Discussionmentioning
confidence: 99%
“…[gentilis] superspecies (sensu Kunz et al 2019) includes two additional species, A. meyerianus and A. melanoleucus. However, no recordings of the 'chattering-type' calls of the A. meyerianus and too few (n=2) of A. melanoleucus were available for study.…”
Section: Methodsmentioning
confidence: 99%
“…Using genomic DNA sequences, Geraldes et al (2019) found a deep divergence between Palearctic and Nearctic populations of A. gentilis. In a detailed mitochondrial DNA study, Kunz et al (2019) showed that Nearctic A. g. atricapillus, A. g. laingi and A. g. apache (hereafter atricapillus-group) and the Palearctic subspecies of A. gentilis (hereafter gentilis-group) formed reciprocally monophyletic groups which were not sister groups because the gentilis-group was closer to Meyer's goshawk A. meyerianus, Henst's goshawk A. henstii and A. melanoleucus than to the atricapillus-group. Kunz et al (2019) suggested that species status may be appropriate for the atricapillus-group but noted that this is best considered in an integrative context, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The considerable morphological variation particularly within A. gentilis has resulted in the acknowledgement of 10 subspecies ( Del Hoyo & Collar, 2015 ; Dickson & Remsen, 2013 ), with the nominate European subspecies, A. gentilis gentilis found across Europe, except for the Iberian Peninsula, southern Italy, and Greece, and extending eastwards to the Carpathians and part of Russia. However, mitochondrial phylogenetic analyses suggest two monophyletic groups within the species, a Neartcic clade and a Palearctic clade ( Kunz et al ., 2019 ).…”
Section: Introductionmentioning
confidence: 99%